Two-week post-operative dressing: balancing cost and surgical site infection risk in orthopaedic procedures - Muhammad, Musa; Maigoro, Aliyu M.; Jimoh, Lamidi; Rufai, Rabiu A.; Salawu, Oni N.; Muhammad, Shamsuddeen; Giade, Sani A.; Jatto, Kabir B.; Yilleng, Shem B. (International Journal of Research in Orthopaedics, 2025)
Background: The study was conducted to determine the safety of having first post-op wound inspection in two weeks following orthopaedic procedures. Methods: It was a retrospective study involving 277 procedures. It involved clean procedures and selected clean contaminated and contaminated procedures. Patients’ records were used to determine the time of first post operative wound inspection. External fixations, sickle cell anemic and diabetic patients were excluded. Wound inspection was categorized before 2 weeks (early) and at or after 2 weeks post-op (delayed). Using southampton wound classification patients were followed for one year to see if there was surgical site infection (SSI). Results: At two weeks, 84.9% patients had normal wound healing and 7.1% had evidence of SSI. 79.73% (n=59) of patients with early wound inspection had normal wound healing while 20.27% (n=15) had evidence of SSI. 97.1% (n=167) of patients with delayed wound inspection had normal wound healing and 2.9% (n=5) had surgical site infection. P value<0.01. At one year, (p value=0.162), 44.44% (n=123) had normal wound healing, 1.08% (n=3) had SSI, 27.80% (n=77) were lost to follow up, 24.19% (n=67) had no available records of their wound conditions, From the 123 with normal wound healing 21.95% (n=27) had early wound inspection, 73.17% (n=90) had delayed inspection. Conclusions: Delayed wound inspection is safe and cost-effective and has less SSI compared to wounds opened early.